A Cross Sectional Study of Secondary Syphilis in A Tertiary Care Hospital (Indian Journal of Applied-Basic Medical Sciences, 2021)
Introduction: Syphilis is a multisystem disease caused by spirochete Treponema pallidum. Syphilis, the great imitator, presents  with a wide range of mucocutaneous and systemic manifestations. Worldwide variety of clinical presentation and  detection of rare morphological variants in 20 th century has created diagnostic difficulty. Therefore, we have conducted this study  to analyse demographic data, clinical presentation and correlated serological findings in patients with secondary syphilis  attending sexually transmitted disease (STD) clinic at a tertiary care center. Method: A retrospective cross-sectional study of the patients with secondary syphilis, detected at the STD clinic from  August 2017 to August 2019 over a period of 2 years was done. Age, sex, occupation, education, complaints, duration, history  of high risk behavior, past history, personal, family and sexual history of the study population were recollected. Result: Among 3241 patients who attended the STD clinic during defined study period, 51 patients were diagnosed as  secondary syphilis. Out of 51 patients included in the study, 40 patients were (78.4%) were male and 11 patients (21.6%)  were female. Most common age group was 21-30 years (47.1%). [Table 1] Discussion and Conclusion: Syphilis by itself was known to be great imitator of various clinical conditions from time being due its multi organ involvement which is seen even in the early stages of infection. This trend of rising homosexual behavior and  HIV infection among adolescents and young adults may lead to altered clinical picture, further adding to the diagnostic  confusion. Hence, sexual history, careful examination and serological testing may help more increasing diagnostic accuracy. There is increased prevalence of secondary syphilis among the males, especially among young males with heterosexual orientation.  In case of lesions over perianal region and atypical presentation should raise suspicion of Homosexual behavior and contact  should be traced properly in this situation. There is increase need of awareness specially among females for early detection  and prevention of spread of sexually transmitted disease. Observations of this study emphasize the urgent need for implementation of programs to focus on sex education and counseling to the adolescents and young adults who  tends to be the vulnerable population in the society. Secondary syphilis is not uncommon entity, so in regular day to day practice as a dermatologist, we should not  miss the diagnosis in case of palmoplanter eczematous lesion and maculopapular rash over trunk.
Keywords: Syphilis; Secondary Syphilis; Tertiary Care Hospital; Cross Sectional Study